Recurrent urinary tract infections in the elderly - Myśliwiec, Michał (Lekarz POZ, 2018)
This paper is a review of the very scanty literature dealing with recurrent urinary tract infection (UTI) in the elderly. Predisposing factors as well as prophylactic general measures and antibacterial drugs are presented. Differentiation of ZUM and treatment of recurrences in women and men, particularly with prostate hypertrophy, are reviewed.